Cognitive and General Health Status in Elderly With and Without History of Falling - Vahid Nejati; Sara Izadi-najafabadi; Otella Shoja; Mehrooz Javadi; Fatemeh Rezaei (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Falling is a main problem in all health systems and approximately 30% of elderly experience one or more falling every year. Cognitive function is known to be a main risk factor for elderly falling. In this study we aim to compare general health and general cognitive status in elderly with and without history of falling. Methods & Materials: In this study 22 elderly without history of falling (15 M, 7 FM) were evaluated and compared with 31 elderly with history of falling (21 M, 10 FM) using general health questionnaire (GHQ) and MMSE. Independent t-test is used for data analysis. Results: Findings showed that differences of general health (P=0.009), and subtest of anxiety and sleep disorder (P=0.004) between two groups are significant. Means comparison showed worst status in elderly with history of falling than those without in general health, sleep disorder, and anxiety. Significant difference between cognitive health score of faller and non-faller elders was seen (P=0.022). Comparing means showed more cognitive impairment in elderly with history of falling than those without history of falling. Conclusion: This study confirms relationship between anxiety, sleep disorder and falling. Sleep disorder may cause falling due to dizziness. Anxiety and fear of falling may cause limited physical activity, balance, and increased risk of falling. Therapeutic methods in reducing anxiety would avoid falling. In addition, cognitive therapy for elderly can reduce the risk of falling.